Strategies of Islamic Religious Education Teachers in Addressing the Negative Effects of Online Gaming on Students at SMPN 1 Atap Pemayungan, Sumay District, Tebo Regency - Sinta Pebri Yenti; Opi Teci Darisma Putri; Mabruri (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The current development of digital technology has brought significant impacts on students’ lives, especially at the junior high school level. One prominent phenomenon is the increasing intensity of online gaming among students. This condition not only affects academic aspects but also has the potential to influence students’ behavior, discipline, and social interactions within the school environment. Therefore, appropriate strategies from Islamic Religious Education (PAI) teachers are needed to address these negative impacts so that they do not interfere with the learning process and students’ character development. This study aims to describe the strategies used by PAI teachers in addressing the negative impacts of online gaming on seventh-grade students at Sekolah Menengah Pertama Negeri Satu Atap Pemayungan. In addition, this study also aims to identify the supporting and inhibiting factors in the implementation of these strategies. The method used in this research is a qualitative approach with a descriptive type of research. Data were obtained through observation, interviews, and documentation involving PAI teachers, students, and school authorities. Data analysis was conducted using data reduction, data presentation, and conclusion-drawing techniques. The results of the study indicate that the negative impacts of online gaming include decreased learning motivation, low concentration in class, and reduced responsibility toward school assignments. To address these issues, the strategies implemented by PAI teachers include providing religious advice, habituating worship activities at school, applying a persuasive personal approach, and collaborating with homeroom teachers and parents in supervising students. The success of these strategies is supported by the school’s religious activity facilities; however, it is hindered by weak parental supervision at home and the influence of peer environments.